Optimization of lignocellulosic biomass-to-biofuel supply chains with densification: Literature review. (January 2021) - Albashabsheh, Nibal T.; Heier Stamm, Jessica L.
Abstract: Densification techniques, such as baling, pelleting, and pyrolysis, help mitigate logistics costs associated with biomass transportation, storage, and handling, but the role of densification within the overall biomass-to-biofuel supply chain context is not yet well understood. This paper reviews the literature for modeling and optimization studies of lignocellulosic biomass supply chains with densification processes. Research studies in academic journals, books, and trade publications are classified based on four criteria: biomass type, densification form, analytical methodology, and densification machines' mobility. We find that baling is the most-studied densification technique, while optimization modeling is the most common analysis method. Although pelleting and pyrolysis achieve a higher density than baling, comparatively few studies have examined their role in the overall supply chain. We identify future research opportunities, the most significant of which are integrating mobile densification and introducing comprehensive biomass-to-biofuel supply chain optimization models. Highlights: Models of biomass-to-biofuel supply chains with densification processes are surveyed. Literature is classified based on densification form and analytical methodology. Baling is the most studied densification form in supply chain models. Optimization is the most common analytical method for supply chain design. Biomass-to-biofuel supply chains with mobile densification are not well studied.